1985
DOI: 10.1111/j.1348-0421.1985.tb00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination of the Decoated Spores of Bacillus megaterium

Abstract: Decoated spores of Bacillus megaterium ATCC 12872 were prepared by extracting the inner coat components with an alkaline solution containing sodium dodecyl sulfate and dithiothreitol (SDS-DTT) from outer coat-deficient mutant spores, which were produced from one of the mutants isolated and named MAE-05 by us. The decoated mutant spores germinated as well as the intact spores of the mutant and the parent, indicating that the outer and inner spore cats cannot be essential structures for the initiation of germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…Wilson and Benoit (1993) and Benoit et al (1995) reported similar observation on the effect of LAA on Btk germination. While many findings reported that coatless spores have decreased rate of germination (Nakatani et al, 1985a;1985b -Bacillus megaterium) or at a rate that comparable to coated spores (Stelma et al, 1978;Kutima and Foegeding, 1987 -Bacillus cereus), the current study showed opposite trend, where rate of germination was increased by removal of spore coat. These results made the influence of coat on germination remain unclear however it may be related to species.…”
Section: Discussioncontrasting
confidence: 72%
“…Wilson and Benoit (1993) and Benoit et al (1995) reported similar observation on the effect of LAA on Btk germination. While many findings reported that coatless spores have decreased rate of germination (Nakatani et al, 1985a;1985b -Bacillus megaterium) or at a rate that comparable to coated spores (Stelma et al, 1978;Kutima and Foegeding, 1987 -Bacillus cereus), the current study showed opposite trend, where rate of germination was increased by removal of spore coat. These results made the influence of coat on germination remain unclear however it may be related to species.…”
Section: Discussioncontrasting
confidence: 72%
“…Such spores can be germinated artificially by addition of cortex-lytic enzymes, such as lysozyme, or spore-specific enzymes (1,4,27). Coatless spores have been observed to germinate at a decreased rate (13,17,18,28), and in somne cases mutants lacking spore coats germinate at a rate comparable to normal spores (26). The exact involvement of the coat and outer membrane in germination is unclear.…”
mentioning
confidence: 99%
“…3B), suggesting strongly that the 48K-protein is a component of the outer coat. On the gel electrophoretic profiles of MAE-05 strain which is an outer coat deficientmutant of B. megaterium (9), the 48K-protein has not been detected in the coat fractions (15), indicating that the 48K-protein is an intrinsic component of the outer coat. Although it was not surprising that the outer coat protein was produced before deposition of inner coat proteins onto the forespore at very early stages, t2-t3, of sporulation, further investigation on the assembly of several coat proteins into the coat layers are required.…”
Section: Methodsmentioning
confidence: 97%
“…We also reported that one of the major coat proteins was 48K-protein, and the synthesis of this protein started at a very early stage, t2, of sporulation (3). The spore coat of B. megaterium ATCC 12872 consists of two major layers, the outer and the inner (9). Figure 3 demonstrates the localization of the 48K-protein in the spore coat.…”
Section: Methodsmentioning
confidence: 99%